Tuning peripheral acceptors in pyran core functional materials to boost photovoltaic efficiency - Mashal Khan; Maria Zafar; Zafar Ullah; Iqra Shafiq; Saifullah Bullo; Tansir Ahamad; Ke Chen (Scientific Reports)
Abstract Non-fullerene acceptors (NFAs) play a crucial role in enhancing the performance of bulk heterojunction organic solar cells (BHJ-OSCs). Therefore, new A–π–D–π–A configured NFAs (BDTD1-BDTD7) were developed from BDTR reference through terminal modification with benzothiophene (BT) based acceptors. Density functional theory (DFT) and time-dependent DFT (TD-DFT) methods were employed at M06/6-311G (d, p) level to explore the geometrical, electronic, optical and photovoltaic properties of the designed derivatives. Lower energy gaps (E gap= 2.130–2.250 eV) and higher absorption wavelengths (λ max = 731.249-775.672 nm in chloroform solvent) were obtained for these chromophores. Least values of binding energy (E b= 0.528–0.554 eV) showed significantly high rate of exciton dissociation which indicated more charge transfer in BDTR and BDTD1-BDTD7. Further, the transition density matrix (TDM), hole-electron and density of states (DOS) graphs also supported the significant charge transfer within titled chromophores. Among all candidates, BDTD5 revealed the best results i.e., least energy gap (2.130 eV) and the bathochromic absorption spectra (775.672 nm). The open-circuit voltage (V oc) was calculated through Scharber’s equation by utilizing PTB7-Th donor. All derivatives showed comparable values of V oc with the reference chromophore (BDTR). Thus, it can be concluded that structural modification through the incorporation of BT acceptors is an effective approach for enhancing the optoelectronic and photovoltaic characteristics of the organic compounds.